2021
DOI: 10.3982/qe1587
|View full text |Cite
|
Sign up to set email alerts
|

Do elite colleges matter? The impact on entrepreneurship decisions and career dynamics

Abstract: Elite college attendance significantly impacts students' entrepreneurship decisions and career dynamics. We find that an elite college degree is positively correlated with entrepreneurship (i.e., owning an incorporated business) but not with other self‐employment forms. Our overlapping generations model captures self‐selection in education and career choices based on heterogeneous ability and family wealth endowments over the life cycle. Our estimates show that (1) entrepreneurs and other self‐employed individ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 61 publications
1
4
0
Order By: Relevance
“…The study also elucidates that the educational institution from which one graduate significantly contributes to compensation determination. Notably, premier institute (institute_Premier = 0.151) and non-premier institute (institute_Non_Premier = 0.065) are pivotal elements, particularly in entry-level IT positions, which is consistent with earlier studies (Herrmann and Nagel, 2023; Guo and Leung, 2021; Carroll et al. , 2019).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The study also elucidates that the educational institution from which one graduate significantly contributes to compensation determination. Notably, premier institute (institute_Premier = 0.151) and non-premier institute (institute_Non_Premier = 0.065) are pivotal elements, particularly in entry-level IT positions, which is consistent with earlier studies (Herrmann and Nagel, 2023; Guo and Leung, 2021; Carroll et al. , 2019).…”
Section: Discussionsupporting
confidence: 89%
“…It is worth mentioning that high compensation is often associated with the prestige and caliber of distinguished institutions such as IIM/IIT/NIT, among others. Graduates from such premier institutions generally receive higher salaries and attain higher-level positions than their non-premier counterparts, as documented in existing literature (Herrmann and Nagel, 2023;Guo and Leung, 2021;Carroll et al, 2019). Moreover, it has been observed that entry-level and associate-level positions are compensated less than management and senior architect positions.…”
Section: Edamentioning
confidence: 79%
“…This paper takes a very different approach and represents the first attempt to quantify all consumption benefits of college that are directly substitutable with other goods, services, 1 Lazear (1977) provides an early analysis of the consumption vs. investment value of education. See, e.g., Keane andWolpin (1997, 2001), Cunha, Heckman, and Navarro (2005), Heckman, Lochner, and Todd (2006), Abbott et al (2019), and Guo and Leung (2020) for estimates of the importance of "psychic/utility/consumption" factors in explaining schooling attendance decisions. See, e.g., Arcidiacono (2004), Rask (2010), Zafar (2013), Gemici and Wiswall (2014), and Wiswall and Zafar (2015) for evidence on the importance of tastes in college major decisions.…”
Section: Introductionmentioning
confidence: 99%
“…See the overview in Mogstad (2017) and related empirical analysis in Houmark, Ronda, and Rosholm (2020). Also related is structural modeling of intergenerational effects (e.g., Lee and Seshadri (2018)) including analysis of multiple types of ability (e.g., Guo and Leung (2021)). mobility.…”
Section: Intergenerational Transmissionmentioning
confidence: 99%